The legislative priority rule and the EU internal market for goods : a constitutional approach - Ni Chaoimh, Eadaoin (Oxford : Oxford University Press, 2022)
Introduces the reader to the Legislative Priority Rule and provides a better understanding of how the European Court of Justice resolves regulatory disputes in the presence of secondary (product) legislation, highlighting both the successes and dangers of its current approach.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 1, 2022).
Keywords: Trade regulation -- European Union countries; Free trade -- European Union countries; Law; Laws of specific jurisdictions & specific areas of law